PERGURUAN TINGGI ISLAM BERBASIS RISET MENYONGSONG BONUS DEMOGRAFI INDONESIA 2045 - Nur Thahirah Umajjah Irha; Muh. Duwana Saide (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2018)
The focus of the study in this paper is “The concept of developing PTKI through a research-based education system in welcoming bonus demographic 2045